El modelo colac como instrumento para medir la estabilidad financiera de las cooperativas de ahorro y crédito del segmento 3, provincia de Tungurahua, periodo 2020 – 2022 - Paltan Tixe, Kelvi Jadira (2024)
ABSTRACT: The main objective of this research study was focused on applying the COLAC model as an instrument to measure the financial stability or instability of the Savings and Credit Cooperatives of segment 3, Tungurahua Province, period 2020 - 2022. In this sense, the specific objectives were to analyze the COLAC model based on the 5 components, to determine the financial risks of the COAC'S, and to identify the high and moderate financial risks in order to establish strategies to address the problem. The methodology applied was based on a descriptive, deductive-inductive method, using field and bibliographic research. Likewise, the design of the study was not experimental, and the approach was mixed. On the other hand, the results showed unfavorable performances in several of the calculated indicators, for which several skills are proposed to be used, depending on the alert linked to these indicators. Along these lines, the co-operative activity indexes, the debt ratio, economic efficiency, administrative efficiency and portfolio delinquency were categorized with a high alert, which means that the co-operatives in the segment should focus their actions on improving the results of these indexes. The recommendations were focused on proposing the improvement of the financial service for people in need, complying with the legal parameters of the SEPS in risk, liquidity and profitability, and planning assets and availability to the client, without cooperative anomalies, maintaining a technical analysis such as the COLAC model.